Physiological, Pathophysiological and Therapeutic Impact of the Enteric Serotonergic System - Molderings, G. J. (Arzneimittelforschung, 2012)
Serotonin (5-hydroxytryptamine, 5-HT) induces various effects in the central nervous system, cardiovascular system and gastrointestinal tract. The response depends primarily on the nature of the 5-HT receptors involved. In the light of the current knowledge about the anatomy and physiology of the serotonergic system and the distribution of the various 5-HT receptors in the gut, the established and potential therapeutic impact of 5-HT receptor ligands are discussed. In particular, selective 5-HT receptor ligands influencing intestinal motility and pain perception such as the 5-HT4 receptor agonist prucalopride appear promising for the treatment of irritable bowel syndrome.
Keywords: serotonin; 5-HT; enteric nervous system; irritable bowel disease; 5-HT receptors